Peptide-containing nerve fibres in the gut wall in Crohn's disease. Issue 8 (August 1983) - Sjölund, K; Schaffalitzky, O B; Muckadell, D E; Fahrenkrug, J; Håkanson, R; Peterson, B G; Sundler, F
Abstract : Neurones containing VIP, substance P, or enkephalin were studied by immunocytochemistry in intestinal specimens from 27 patients with Crohn's disease. Also several endocrine cell systems in the gut were examined. The results were compared with those from a control group of 26 patients. The relative frequency of various endocrine cells did not differ overtly from that in controls. Vasoactive intestinal polypeptide and substance P nerve fibres were distributed in all layers of the gut wall, including the submucosal and myenteric plexuses, whereas enkephalin fibres were restricted to the smooth muscle layer and the myenteric plexus. The distribution and frequency of the peptide-containing nerve fibres were the same in Crohn's disease patients as in control patients. A proportion of these nerve fibres, however, were notably coarse in the Crohn's disease patients. This was particularly apparent in the afflicted parts of the intestine although it was noted also in non-afflicted parts. The concentration of VIP and substance P (expressed as pmol/g wet weight) did not, however, exceed that of the control group.